MENCIPTAKAN LINGKUNGAN SEKOLAH YANG EFEKTIF - Hendrizal Hendrizal (Program Studi PGSD FKIP Universitas Bung Hatta, 2019)
This paper intends to review efforts to create a conducive and effective school environment more intensively so that learning objectives become more quality can be achieved. The purpose of making this paper is to be able to give insight to those who take part in the world of education to increasingly understand the following: the problem of the concept of the school environment and the concept of an effective school environment. It is known that to create an effective school environment there needs to be collaboration and compatibility between the conditions of the learning environment, both the physical and social environment, with the learning participants in this case students and teachers. Both learning environments need to be maximized in order to create an effective school environment. At the level of praxis, furthermore, it is hoped that education personnel can apply an understanding of the concept of the school environment and the concept of an effective school environment in organizing educational and schooling activities.